Effectiveness of aerobic physical exercise on depression symptoms in adults: A protocol for developing a systematic review and meta-analysis of randomized clinical trials - Larissa Nayara de Souza; Silvana Medeiros de Araújo; Eva da Silva Paiva; Alícia Eliege da Silva; Joel Florêncio da Costa Neto; Juvêncio César Lima de Assis; Isis Kelly dos Santos; Themis Cristina Mesquita Soares; Edson Fonseca Pinto; Roque Ribeiro da Silva Júnior; Maria Irany Knackfuss (PLoS ONE, 2025)
Background Depression is a chronic condition that affects millions of people and requires effective interventions. Studies suggest that aerobic exercise can improve mental health and reduce depression symptoms, despite variations in exercise type and intensity. Objective This article presents a protocol for conducting a systematic review with meta-analysis, aimed at investigating the effects of aerobic exercise on reducing depression symptoms in adults. Methods This is a systematic review protocol, which will follow the PRISMA-P 2020 guidelines and has been registered in PROSPERO (no. CRD42024592700). The study search will be conducted in six databases: BVS, Cochrane library, Embase, Epistemonikos, PubMed and SPORTDiscus, using MeSH-based descriptors. Studies will be selected independently by two researchers using the Rayyan ‘QCRI’ software. Data extraction will be performed using specific forms, while the methodological quality of studies on physical exercise will be assessed with the TESTEX tool, and the risk of bias will be evaluated using the Cochrane RoB 2.0 method. The certainty of evidence will be evaluated through the Grading of Recommendations Assessment, Development, and Evaluation (GRADE). Conclusions It is expected that the systematic review following this protocol will identify the effective dose-response to reduce depression levels and provide an understanding of the mechanisms through which aerobic exercise influences depression.